Effects of proprioception training program on balance among patients with diabetic neuropathy: a quasi experimental trial - Humaira Iram; Muhammad Kashif; Hafiz Muhammad Junaid Hassan; Salma Bunyad; Samra Asghar (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effects of proprioception training in improving balance in patients with diabetic neuropathy. Methods: A quasi-experimental design study was conducted at the Safi Hospital Faisalabad for eight weeks from August to December 2019. Out of, 38, 19 patients were placed in exercise group (10 males, 9 females; mean age 64 ± 7.7 years; range 60 to 83 years) and 19 patients were placed in controls group (12 males, 7 females; mean age 63 ± 8.2 years) were included in this study through consecutive sampling technique. Proprioception Training was given to exercise group twice a week for eight weeks and the diabetes awareness campaign was given once a week to the control group. Static and dynamic balance were assessed by using One Leg Standing (OLS) Test with eyes open and closed, Berg Balance Scale (BBS), Functional Reach Test (FRT), Timed Up and Go Test (TUGT) and 10-M Walk Test (10-MWT). The data was collected before and after treatment and was compared using independent sample t-test. Results: The finding of the study showed that OLS score with eyes open improved significantly with p<0.05 and does not show improvement with eyes closed p =.073. The dynamic balance from the Berg Balance Scale, Functional Reach Test, Timed Up and Go Test and 10-M Walk Test revealed significant improvement after the balance exercises with p<0.05 Conclusion: It is concluded that proprioception training exercises are effective in improving balance among patients with Diabetic neuropathy. Continuous...